Challenges and Perspectives of Sustainable Development for Children Affected by Armed Conflicts in Africa: A Case Study from the Democratic Republic of the Congo - Mariame Viviane Nakoulm, Mariame Viviane Nakoulm (Children’s Rights in the Sustainable and Digital Environments: Exploring Opportunities and Challenges, 2025)
Children are extremely vulnerable in times of conflict and crisis. In 2022, more than two-thirds of the world’s children were living in a conflict-ridden country. The arguments raised in this contribution are contextualized and introduced into the broader reflection on the merits of the adoption, in 1989, of the Convention on the Rights of the Child (CRC). Our findings and recommendations aim justly to highlight how the implementation of this instrument shaped the African system in protecting the child, and explore the ways in which children's rights and armed conflict interact, as the situation in the Democratic Republic of the Congo is still attesting to it.